STRATEGI PERENCANAAN PENGEMBANGAN PENDIDIKAN DASAR DI KABUPATEN RAJA AMPAT - , Alfaris Mambraku, S.E., Dr. Wahyu Widayat, M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
As a currently developing region, Raja Ampat Regency extremely need the adequate subsector system of elementary education in view of number of teachers, curricula, infrastructure, childen participation level in school attendance, learning and teaching processes, teaching personnel quality, education aid, the involvement of headmaster as a class teacher, the education-based job placement of teacher, the role of school inspection personnel and so on. Therefore, it is necessary to identify strategies for elementary education development that should be done based on the dimensions of strengths, opportunities, weaknesses, and threats that can be found in elementary education subsector in Raja Ampat Regency. This study used a descriptive qualitative method with a case study design. Location of the study was in Raja Ampat Regency. Data used were primary data, i.e. those obtained through interview, and secondary data, i.e. those obtained by a documentary study. The data collected were then analyzed by using a qualitative technique. Result of the study indicates that Raja Ampat Regency had many strengths potentially prioritized for elementary education development. The highest score of SWOT dimensions in elementary education development in Raja Ampat Regency were Opportunities (699), followed by Strengths (677), Threats (551), and Weaknesses (346). From the results, Government of Raja Ampat Regency, particularly Office of Education and Teaching, it is necessary to emphasize the dimensions of Strength and Opportunity with most scores as bases for formulating the strategies of elementary education development. Among priorities necessary to emphasize are the equation and increase of education quality, particularly elementary school level. The purpose is that the Office of Education and Teaching can implement the Education Unit Level Curriculum (Kurikulum Tingkat Satuan Pelajaran - KTSP) in a more optimum manner as applied by other more advanced regions throughout Indonesia, particularly in Java Island. Moreover, the increase of human resources is directed to the placement of teaching and educational personnel with the needs of elementary education in Raja Ampat Regency. To support the human resources improvement, elementary school infrastructure revitalization program is necessary to be done immediately with damage severity. Finally, to increase the integrated elementary education implementation in Raja Ampat Regency, the Office of Education and Teaching should enhance coordination with many related parties to support school programs.